120k views
2 votes
solving the equation, james realized that he made an error. which step was the error and what is the correct answer?-4(10n - 6) = -406-40n - 6 = -406 STEP 1 -40n - 6 + 6 = -406 + 6 STEP 2-40n = -400 STEP 3-40 n/ -40= 400/ -40 STEP 4n=10 STEP 5

User Tbaz
by
5.4k points

1 Answer

4 votes

-4(10n-6)=-406

1. You remove the parenthesis, the term outside the parenthesis affect each term in the parenthesis (you multiply -4 for each term in the parenthesis):


\begin{gathered} -4(10n)-4(-6)=-406 \\ -40n+24=-406 \end{gathered}

The mistake was in the step 1 as the -4 was not multiplied for both terms in the parenthesis.

2. Substract 24 in both sides of the equation:


\begin{gathered} -40n+24-24=-406-24 \\ -40n=-430 \end{gathered}

3. Divide into -40 both sides of the equation:


\begin{gathered} (-40n)/(-40)=(-430)/(-40) \\ \\ n=(430)/(40) \end{gathered}

4. Simplify:


n=(430)/(40)=(43)/(4)=10.75Then, the answer is n=10.75
User Brissles
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.